Pengaruh Kompensasi dan Work-Life Balance terhadap Loyalitas Guru di Sekolah Dasar Negeri di Kecamatan Samarinda Kota - Muhammad Faisal; Praja Hadi Saputra; Yulia Tri Kusumawati (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to determine the influence of compensation and work-life balance on teacher loyalty at public elementary schools in Samarinda Kota District. This research employed a quantitative approach with a sample of 93 respondents consisting of ASN (civil servant) and non-ASN teachers from SDN 005, SDN 006, SDN 007, and SDN 011 in Samarinda Kota District. Data collection was conducted through the distribution of questionnaires. The independent variables in this study were compensation (X1) and work-life balance (X2), while the dependent variable was teacher loyalty (Y). Data analysis involved validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests for model feasibility (Goodness of Fit), and the coefficient of determination test (R²). The results showed that both compensation and work-life balance have a positive influence on teacher loyalty. Improvements in fair compensation and the creation of a balance between work and personal life can enhance teachers' loyalty to their respective schools. The Goodness of Fit test indicated that the regression model used in this study met the feasibility criteria and was significant, making it appropriate for predicting teacher loyalty in public elementary schools in Samarinda Kota District.